2017
DOI: 10.1039/c7sm01645j
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and structural characteristics of polyelectrolyte multilayers used as cushions for supported lipid bilayers

Abstract: The surface properties of polyelectrolyte multilayers (PEMs) obtained via sequential adsorption of oppositely charged polyions from their solutions and used as cushions for supported lipid bilayers were investigated. Five types of polyelectrolytes were used: cationic polyethyleneimine (PEI), poly(diallyldimethylammonium)chloride (PDADMAC), and poly-l-lysine hydrobromide (PLL); and anionic polysodium 4-styrenesulfonate (PSS) and poly-l-glutamic acid sodium (PGA). The wettability and surface free energy of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…Moreover, hydrogen bonding formation among PE lipids and between the PE headgroup and the solid support could promote vesicle fusion and SLB formation. 44,45 The PEI film has been previously shown [46][47][48][49][50] as an effective anchor for subsequent adsorption of nanoobjects such as polyelectrolytes, nanoparticles, or liposomes. In our study, the PEI monolayer preparation used the same procedure as that in these studies, and the detailed characterization of such PEI monolayers has also been reported by Adamczyk et al.…”
Section: 20mentioning
confidence: 99%
“…Moreover, hydrogen bonding formation among PE lipids and between the PE headgroup and the solid support could promote vesicle fusion and SLB formation. 44,45 The PEI film has been previously shown [46][47][48][49][50] as an effective anchor for subsequent adsorption of nanoobjects such as polyelectrolytes, nanoparticles, or liposomes. In our study, the PEI monolayer preparation used the same procedure as that in these studies, and the detailed characterization of such PEI monolayers has also been reported by Adamczyk et al.…”
Section: 20mentioning
confidence: 99%
“…In contrast, roughness parameters of the (wPE) 9 GO film are higher than that of the wPE film. This difference can be attributed to the distinct growth mechanism of multilayers composed of interpenetrating vs non‐penetrating PE which has been shown to affect the surface properties of PEM films …”
Section: Resultsmentioning
confidence: 99%
“…As the evaporation took place, the pinned droplet would thin, and the apparent CA at the pinned periphery would decrease to the values of respective nano/microfluids, before the contact line receded upon further evaporation. (38)(39)(40). Resolving this small controversy is beyond the scope of this study.…”
Section: Substrate Characterization: Surface Energy and Roughnessmentioning
confidence: 95%